Environmental behaviors and ecotoxicity of imidaclothiz: a comprehensive review on fate, degradation processes, and ecological risks - Yang, Ju; Chen, Hao; Song, Ke-Wei; Chen, Yi-Fei; Shen, Yue; Li, Wen-Jing; Li, Xiao-Fang; Zhai, Peng-Fei; Zhao, Yun-Xiu (Frontiers in Microbiology, 2026)
Neonicotinoid insecticides (NEOs) are among the most widely used pesticide classes globally, primarily applied to control crop pests and vector plant pathogens. As a fourth-generation NEO, imidaclothiz (IMT) has seen rapidly expanding agricultural use across Asia—particularly in China—in recent years. However, increasing evidence highlights the persistence of NEO residues in the environment and their toxic effects on non-target organisms. The frequent detection of NEOs in aquatic systems indicates growing contamination that may pose significant risks to human and ecosystem health. Microbial degradation, alongside chemical pathways, plays a crucial role in mitigating the environmental impacts of these pesticides, with microbial remediation emerging as a promising ecological strategy. Nevertheless, current research on IMT remains limited: only a few IMT-degrading microorganisms and key metabolic enzymes (e.g., cytochrome P450s, manganese peroxidases) have been identified, and systematic mechanistic studies are largely lacking. Moreover, the ecotoxicity effects of IMT and its environmental transformation products—particularly their broader ecological implications—are poorly synthesized and insufficiently understood. This review provides a comprehensive assessment of the environmental behavior, degradation mechanisms, and ecotoxicity impacts of IMT, offering critical insights into the multiscale environmental risks of NEOs and supporting future ecological risk assessments and sustainable pesticide management.